Hotel location in Africa’s world class city: The case of Johannesburg, South Africa. - Rogerson, Jayne M. (Bulletin of Geography. Socio-economic Series, 2014)
Urban tourism is of rising importance for economic and tourism geographers. One of the most important elements for urban tourism is the hotel economy. Against a backdrop of international debates around the location of hotels in cities in both developed and developing countries this article unpacks the changing geography of hotels in South Africaâs largest city, Johannesburg for the period 1990 to 2010. Johannesburg is one of the leading and growing destinations for urban tourism in South Africa. Its hotel scape has been radically transformed in the past two decades. It is shown that the shifting geography of hotel development in Johannesburg reveals a complex pattern of disinvestment in certain city spaces and subsequent reinvestment and re-vitalization of those spaces as well the changing patterns of hotel investment towards the new successful nodes of business and leisure tourism in the city.